Depressive symptoms among older empty nesters in China: the moderating effects of social contact and contact with one's children. (2nd January 2023) - Xu, Mingming; Yang, Wei
Abstract: Objectives: Mental health for older people has become a major social concern. Literature has shown that older people, especially when they become empty nesters—when a parent lives alone or lives with his/her spouse after the youngest child leaves home—may start to develop various mental health problems due to reduced contacts with their children. Using fixed-effects, multivariate regression with a difference-in-differences approach and propensity score matching, this paper examines the relationship between being an empty nester and mental health among older people in China, and the moderating effects of social contact and contact with one's children in terms of mental health. Our data come from the China Health and Retirement Longitudinal Study of 2011, 2013, 2015 and 2018. Results: We found that, in the short term, the mental health of older people may not be affected after they became empty nesters. But in the longer term, if they did not have regular contact with their children, their mental health would deteriorate with time. Social contact, especially cognitive activities, was beneficial to the mental health of the older empty nesters. We also found that for older empty nesters with disabilities, frequent social contact and contact with their children were more important. Conclusion: We urge the government to promote community-based social activities for older people, especially for those with functional limitations.